THE FLUID REGIME OF HIGH-TEMPERATURE METAMORPHISM DURING GRANITOID MAGMA GENESIS - Clemens J.D.; Watkins J.M. (My University, 2001)
The strong negative correlation between the temperatures and melt H2O contents of granitoid magmas implies that the crustal melting reactions that produced the magmas were strongly buffered, with T and aH2O co-varying within a narrow band. This observation can only be explained if the partial melting reactions that created the magmas were either fluid-absent from the outset or evolved toward this condition as melting progressed. Since these melting reactions occur during upper amphibolite- to granulite-facies metamorphism, it is reasonable to conclude that metamorphic events responsible for the generation of granitoid magmas generally occur in the absence of excess pervasive fluid.